Odpowiedzi

2010-03-25T22:29:38+01:00
2010-03-25T22:32:23+01:00
A)5²-15x= 5(5-3x)
b)3by-6b= 3b(y-1)
c)-8xy+8x= 8x(-y+1)
d)10a²-2ab= 2a(5a-b)
e)xy-x2y= xy(1-2)
f)6a-24b+30c= 3(2a-8b+10c)
g)12ab²+18b²=6ab²(2+3a)
i)x³-2x²+x= x(x²-2x+1)
j)2xy+3x-x²y= x(2y+3-xy)
2010-03-25T22:45:29+01:00
Kolega/koleżanka wyżej się pomylił/pomyliła w niektórych rozwiązaniach:

b)3by-6b= 3b(y-1) ma być --> b)3by-6b= 3b(y-2)

e)xy-x2y= xy(1-2) w takim razie = xy-2xy (tam chyba x² ma byc nie x2y) więc ---> e)xy-x2y= xy(1-x)

f)6a-24b+30c= 3(2a-8b+10c) można bardziej rozpisac ---> f)6a-24b+30c= 6(a-4b+5c)

g)12ab²+18b²=6ab²(2+3a) błedne rozwiązanie! ---> g)12ab²+18b²=6b²(2a+3)